2005
DOI: 10.1111/j.1365-2966.2005.09621.x
|View full text |Cite
|
Sign up to set email alerts
|

The baseline intracluster entropy profile from gravitational structure formation

Abstract: The radial entropy profile of the hot gas in clusters of galaxies tends to follow a power law in radius outside of the cluster core. Here we present a simple formula giving both the normalization and slope for the power‐law entropy profiles of clusters that form in the absence of non‐gravitational processes such as radiative cooling and subsequent feedback. It is based on 71 clusters drawn from four separate cosmological simulations, two using smoothed particle hydrodynamics and two using adaptive‐mesh refinem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
445
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 309 publications
(519 citation statements)
references
References 42 publications
70
445
4
Order By: Relevance
“…Once again, the data are compared with the results of the spectroscopic X-ray analysis, which highlights the much broader radial range accessible by the joint X-ray/SZ technique. The observed entropy profiles are compared with the prediction of numerical simulations using gravitational collapse only (Voit et al 2005).…”
Section: Joint X-ray/sz Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Once again, the data are compared with the results of the spectroscopic X-ray analysis, which highlights the much broader radial range accessible by the joint X-ray/SZ technique. The observed entropy profiles are compared with the prediction of numerical simulations using gravitational collapse only (Voit et al 2005).…”
Section: Joint X-ray/sz Analysismentioning
confidence: 99%
“…The thermodynamical properties of the gas retain information on the processes leading to the thermalization of the gas in the cluster's potential well, which is encoded in the gas entropy K = kT n −2/3 e . Gravitational collapse models predict that the entropy of stratified cluster atmospheres increases steadily with radius, following a power law with index ∼ 1.1 (Borgani et al 2005;Sembolini et al 2016;Voit et al 2005). However, nongravitational processes induce an additional injection of entropy and can therefore be traced through the departures from the theoretical predictions (Chaudhuri et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical models and hydrodynamic simulations of halo formation neglecting radiative cooling have shown that the radial profile of the specific entropy of the hot gas generated by accretion shocks roughly follows a powerlaw function of radius with a power index β ∼ 1.1 (e.g. Tozzi & Norman 2001;Voit, Kay & Bryan 2005;Lu & Mo 2007). When radiative cooling is included, the entropy profile can be modified.…”
Section: Configuration Of the Hot Halo Gasmentioning
confidence: 99%